Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jare.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic hyperuricemia and chronic kidney disease: Narrative review of a treatment controversial

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 78 publications
(130 reference statements)
5
52
0
3
Order By: Relevance
“…Large randomized clinical trials on treatment of hyperuricemia for primary or secondary CKD prophylaxis are underway in populations with hypertension. 39 Our results also indicated that patients in the third tertile UA group were significantly more often treated with thiazide diuretics. It is well know that thiazide diuretics induce hyperuricemia.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Large randomized clinical trials on treatment of hyperuricemia for primary or secondary CKD prophylaxis are underway in populations with hypertension. 39 Our results also indicated that patients in the third tertile UA group were significantly more often treated with thiazide diuretics. It is well know that thiazide diuretics induce hyperuricemia.…”
Section: Discussionsupporting
confidence: 60%
“…However, these trials were of limited duration and included only small number of patients. Large randomized clinical trials on treatment of hyperuricemia for primary or secondary CKD prophylaxis are underway in populations with hypertension …”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia is a known risk factor for the development and progression of CKD [68]. However, according to the KDIGO guideline there is insufficient evidence to support or refute the use of agents to lower serum uric acid concentrations in people with CKD and either symptomatic or asymptomatic hyperuricemia in order to delay the progression of CKD.…”
Section: Hyperuricemiamentioning
confidence: 99%
“…Hyperuricemia is defined as a serum UA level > 416 µmol/L in males and >357 µmol/L in females [1]. There are several ways to define UA: (i) a statistical definition that defines high uric acid (HUA) as serum (S)UA lying more than 2 standard deviations above the mean (>458 µmol/L in men or >393 µmol/L in women) [2]; (ii) a physicochemical definition of HUA, taking into account the saturation point for monosodium urate crystals (≥357 mcmol/l) [3]; (iii) a risk definition based UA values associated with an increased cardiovascular risk (476 or 535 mcmol/l as the limit to begin treatment) [4] or (iv) a risk for kidney function definition based on upper limited expected SUA values according to serum creatinine (SCr <0,132 µmol/L: SUA >535 µmol/L, SCr 0,132-0.176 µmol/L: SUA >595 µmol/L, and SCr >0.176 µmol/L: SUA >714 mg/dL [5]).…”
mentioning
confidence: 99%
“…Asian patients with end-stage renal disease (ESRD) present higher rates of HUA, and men have a higher risk of HUA and gout in the general population [7]. Data from several studies have associated HUA with increased incidence and/or progression of CKD [2,4,[7][8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%